Epitope Analysis of Cerebrospinal Fluid IgG in Japanese Multiple Sclerosis Patients Using Phage Display Method. (10th November 2011) - Fujimori, Juichi; Nakashima, Ichiro; Fujihara, Kazuo; Misu, Tatsuro; Sato, Shigeru; Itoyama, Yasuto
Abstract : To investigate the antigen recognized by cerebrospinal fluid (CSF) high affinity IgG in patients with multiple sclerosis (MS), the phage display method was applied to the CSF from 15 MS and 10 control patients. Peptide sequences recognized by MS and control CSF IgG were individual specific, and no common motif was found. Peptide sequences frequently showed homology to various kinds of amino acid sequences of ubiquitous viruses such as epstein barr virus (EBV) and herpes simplex virus (HSV), although the frequency was not specific to MS patients. MS CSF IgG may recognize various types of ubiquitous viral antigen and may be increased by a bystander response.